2021
DOI: 10.3934/mbe.2021462
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization and chimera states in the network of electrochemically coupled memristive Rulkov neuron maps

Abstract: <abstract> <p>Map-based neuronal models have received much attention due to their high speed, efficiency, flexibility, and simplicity. Therefore, they are suitable for investigating different dynamical behaviors in neuronal networks, which is one of the recent hottest topics. Recently, the memristive version of the Rulkov model, known as the m-Rulkov model, has been introduced. This paper investigates the network of the memristive version of the Rulkov neuron map to study the effect of the memri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…To quantize the solitary nodes and determine the extent of synchronization in the system after a satisfactory number of iterations, we employ two metrics known as the cross-correlation coefficient [30,55] and the synchronization error [64]. We also realize the complexity of the time series data that get generated from our simulations using a measure known as sample entropy.…”
Section: Quantitative Metrics and Time Series Analysismentioning
confidence: 99%
“…To quantize the solitary nodes and determine the extent of synchronization in the system after a satisfactory number of iterations, we employ two metrics known as the cross-correlation coefficient [30,55] and the synchronization error [64]. We also realize the complexity of the time series data that get generated from our simulations using a measure known as sample entropy.…”
Section: Quantitative Metrics and Time Series Analysismentioning
confidence: 99%
“…The synchronous firing and chimera state were observed in a ring neuron network constructed with memristorcoupled discrete Chialvo neurons. [34] Mahtab Mehrabbeik et al [35] studied the memristive Rulkov neuron maps and analyzed the synchronous dynamics under electrical and chemical coupling. Their results shows that two m-Rulkov neurons can achieve synchronization only when electrically coupled, but not when chemically coupled.…”
Section: Introductionmentioning
confidence: 99%
“…Sausedo-Solorio and Pisarchik [22] considered the Rulkov maps with memory and synaptic delay and observed lag or anticipated synchronization. The network of the memristive version of the Rulkov model was studied by Mehrabbeik et al [23]. They showed that in contrast to the original Rulkov models, two electrically coupled memristive Rulkov maps could reach complete synchronization.…”
Section: Introductionmentioning
confidence: 99%